From Persons of Indian Origin to Overseas Citizen of India: The South African Indian diaspora and India’s economic diplomacy - Moosa, Fatima (University of the Witwatersrand, Johannesburg, 2024)
The India diaspora is one of the largest in the world with around 17.9 million people from India and/or of Indian descent living around the world (Challagalla 2018, 3). A large percentage of the diaspora is situated in the Global North and the Middle East. However, South Africa has been noted as having one of the largest Indian diasporic populations (Hofmeyer and Williams 2001,14). The migration of Indian people to South Africa has taken place over different periods. The relationship that exists between the diaspora and the country of origin in the spheres of economic and development diplomacy presents an interesting research topic. This dissertation will seek to understand what role, if any, the South African Indian diaspora plays in the international political economy of India. In order to understand the relationship between the diaspora and the Indian government, this dissertation will examine the bilateral relationship between South Africa and India from 1994 until 2022. There will be a specific focus on the years 2014 until 2022 with an analysis of the relationship between the South African Indian diaspora and India. This dissertation will seek to understand whether the diasporic policies and economic diplomacy enacted by the Modi government were directed at the South African Indian diaspora, how they were received by the South African Indian mercantile community and what were the reasons for the foreign policy.
A research report submitted in partial fulfillment of the requirements for the degree of Masters of Arts in International Relations to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Indian Origin; Overseas Citizen of India; South African Indian diaspora; India’s economic diplomacy; SDG-10: Reduced inequalities